Sulfasalazine-Induced Reaction Cascade - Kaustav Saha; Shatavisa Mukherjee (Wolters Kluwer Medknow Publications, 2024)
Sulfasalazine, a relatively well-tolerated, disease-modifying anti-rheumatoid drug has been reported to be associated with hepatic and cutaneous adverse events, in addition to its common adverse effect profile. The present case reports a reaction cascade involving hepatic, ocular, and cutaneous reaction in a female patient secondary to her sulfasalazine use. The report highlights the importance of multidisciplinary teamwork in the treatment and adverse event management in these cases, to help patients with better and safer treatment outcomes.